Does Governance Cause Growth? Evidence from China. (March 2016) - Wilson, Ross
Highlights: I test causality between quality of governance and economic growth in China. Economic growth causes subsequent governance improvements. Improvements in governance do not cause economic growth. Summary: This study tests the causal relationships between quality of governance and economic growth at the provincial level in China during the post-Mao reform era. Exploiting the wide cross-provincial variation and rapid change over time in governance institutions and economic performance in China during this period (covering 1985–2005), the study provides a new perspective on the relationship between governance and growth. Whereas a large body of prior literature has demonstrated a strong positive association between high-quality governance institutions and good economic performance at the cross-country level, few quantitative studies have explicitly tested the direction of causality between changes in governance quality and changes in economic outcomes. This study aims to address this gap in the literature by testing two causal hypotheses on the interplay between provincial-level governance and economic performance in China: (i) improvements in provincial quality of governance predict subsequent economic growth rates, and (ii) increases in provincial economic growth rates predict subsequent changes in quality of governance. Using new heterogeneous Granger causality tests that allow for potential differences in the causal relations across provinces, I show a significant and positive effect of economic growth on subsequent quality of governance, largely driven by growth in the secondary sector, but no significant effect of quality of governance on economic growth. These findings suggest that improvements in formal governance have not been a key factor driving China's rapid growth; instead, the observed positive association between governance and growth reflects the ability of provincial governments to harness the potential created by economic growth to implement subsequent governance improvements. For researchers studying the effect of governance on growth, the results suggest that greater attention should be paid to possible reverse causality from economic outcomes to governance changes.